Ulcerative Sarcoidosis: Confusing Case Report (Texas Journal of Medical Science, 2021)
Along with the most frequent and characteristic (typical) forms of specific cutaneous sarcoidosis, there are a great variety of clinically atypical granulomatous cutaneous lesions have been described, accordingly, rarely diagnosed, which are usually observed in patients with visceral sarcoidosis. There are many atypical forms of the disease, which complicates the clinical diagnosis of sarcoidosis, the diagnosis of which can be made as a result of histopathological examination. The literature describes in sufficient detail the morphological criteria for the histopathological diagnosis of the granulomatous process of sarcoidosis, which will be identical both in typical and atypical forms of sarcoidosis. In our article, we present difficulties in the diagnosis of atypically occurring sarcoidosis of the skin even with a morphological study. Diagnosis was hindered by the clinical similarity of this disease to lupoid cutaneous leishmaniasis in a 58-year-old patient. The final diagnosis was made only after corticosteroid therapy.